Antioxidative properties of defatted dabai pulp and peel prepared by solid phase extraction - Khoo, Hock Eng; Azlan, Azrina; Ismail, Amin; Abas, Faridah (MDPI, 2012)
Solid phase extraction (SPE) using Sep-Pak® cartridges is one of the techniques used for fractionation of antioxidant compounds in waste of dabai oil extraction (defatted dabai parts). The aim of this study was to determine the phenolic compounds and antioxidant capacity in crude extracts and several SPE fractions from methanolic extract of defatted dabai pulp and peel. Based on SPE, Sep-Pak® cyanopropyl and C18 cartridges were used to fractionate the antioxidant-rich crude extracts into water and methanolic fractions. Analyzed using LC-MS, flavonoids, anthocyanins, saponin derivatives and other unknown antioxidative compounds were detected in the defatted dabai crude extracts and their SPE fractions. Anthocyanins were the major phenolic compounds identified in the defatted dabai peel and detected in most of the SPE fractions. Methanolic fractions of defatted dabai parts embraced higher total phenolics and antioxidant capacity than water fractions. This finding also revealed the crude extracts of defatted dabai peel have the most significant antioxidant properties compared to the methanolic and water fractions studied. The crude extract of defatted dabai parts remain as the most potent antioxidant as it contains mixture of flavonoids, anthocyanins and other potential antioxidants.